The efficacy of online distance learning (ODL) versus conventional learning mode in the final year project (FYP) course of engineering undergraduate / Adnan Derahman ... [et al.] - Derahman, Adnan; Hamzah, Noorfaizah; Mat Yusof, Nur’Ain; Roslan, Nur Alifah Ilyana; Mohammad Noh, Noorasyikin (2024)
Periodic positive carrier data from the COVID-19 outbreak in Malaysia intensified government efforts to enforce the movement control order (MCO); Malaysians must remain at home to prevent the virus from spreading fast. The sequence of movement control has an impact on the undergraduates of the Final Year Project (FYP). Undergraduate students from the College of Engineering were instructed to stay at home and utilising the Online Distance Learning (ODL) mode as they were unable to continue their FYP in a conventional approach. The repercussions of the online approach as a teaching and learning tool were implemented as an alternative for student to perform their FYP accordingly. A survey was done among the 302 undergraduate students to assess their satisfaction with the ODL approach during the pandemic, to highlight the challenges they experienced, and to determine the most effective learning mode for FYP. The ODL mode has been implemented globally and does not impair future immersive learning and foster exceptional accomplishment of the FYP. The effectiveness of Open and Distance Learning (ODL) in the Final Year Project (FYP) was demonstrated by the survey results, which indicated the students' satisfaction with their accomplishments. The findings reveal a clear inclination towards Open and Distance Learning (ODL), with 45.7% of participants indicating contentment, in contrast to only 20.2% for traditional classroom-based learning. It may be inferred that the majority of respondents in the Engineering Program's Final Year Project (FYP) are more satisfied with Open and Distance Learning (ODL) compared to traditional classroom learning.